The Stratification of Organic Carbon and Nitrogen in Top Soils as Affected by the Management of Organic and Conventional Rice Cultivation - Anshori, Arif; Pramono, Ali; Mujiyo, Mujiyo (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Organic and conventional management in rice cultivation have an impact on the nature of soil and the sustainability of agricultural system. This study aimed to determine the stratification of organic carbon and nitrogen in top soil from organic and conventional rice management. Top soil samples from organic and conventional rice management were taken before planting rice to find out the parameters of several soil characteristics. After rice was planted, top soil samples were taken at the depths of 0-4, 4-8, 8-12, 12-16, 16-20, 20-24 and 24-28 cm from organic and conventional rice fields, to determine the total organic carbon, total nitrogen and nitrate. The results show that organic rice management will provide better soil properties. Stratification of organic carbon and nitrogen was found in top soil from organic and conventional rice fields. Organic rice field appeared to have organic carbon content that was significantly higher than that of conventional rice field, and it is concentrated on top soil surface. The total nitrogen content in layers 0-4 cm and 4-8 cm in organic rice field was considerably higher than in conventional, but the content was different in layers 8-24 cm. Nitrate content was significantly different in top soil 12-16, 16-20 and 20-24 cm, significantly in top soil 8-12 cm, with nitrate in top soil of conventional rice field higher than in organic rice field. However, it was not significant in 0-4 cm and 4-8 cm top soils. This condition was influenced by organic and synthetic chemical fertilization, nitrification, denitrification and leaching.